Quando a linguagem é imprescindível à sobrevivência: Ó, de Nuno Ramos - Mayara Ribeiro Guimarães (Estudos de Literatura Brasileira Contemporânea)
Developing the well known literary theme of the organic relationship between body and language, Ó, novel by Nuno Ramos published in 2008, touches the boundaries involving body, death and writing, from the perspective of the language crisis opened up by the experience of aging and body decay. The crisis leads to a non-recognition between the subject and the body, identity and language, which, as a result, engenders a language comitted to the experience of drifting. This experience is then staged by the dialogue of literary tradition and the rupture provoked in language by the contact with the residual. Following this track, Nuno Ramos’ novel breaks lose from the traditional concept of realism and representation in literature on behalf of the staging of both literary tradition and the act of writing. This essay tries to portrait the problems engaged in this novel involving the debate of how contemporary brazillian literature brings back important issues questioned by brazillian literary tradition represented by pioneers of contemporary literature, such as Clarice Lispector.